The Azerbaijani Diaspora in Modern Kazakhstan - Kaldybayev, М.С.; Yarygin, С.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
. The object of research in the article is the Azerbaijani diaspora. The introduction touches on the early stages of the history of Oguz tribes in Kazakhstan and in adjacent territories. The history of formation of the Azerbaijani diaspora, its periodization and determining factors are considered. Based on the data of a number of population censuses and modern statistics, the change in the number of Azerbaijanis in Kazakhstan is monitored, the use of statistical data makes it possible to trace the dynamics of migration processes, in particular the external migration of Azerbaijanis in the territory of Kazakhstan in the last two decades, and to reveal the extent of migration impact on the Azerbaijani diaspora. The current state of the Azerbaijani diaspora is analyzed, the data on the structure of settlement of Azerbaijanis in the regions of the Republic of Kazakhstan, the level of urbanization in different periods, age structure, education and incomes are given. A comparative analysis of some data on Azerbaijanis and other ethnic groups of Kazakhstan is carried out.